1973
DOI: 10.5558/tfc49174-4
|View full text |Cite
|
Sign up to set email alerts
|

Hail damage to a new white spruce and lodgepole pine plantation in central British Columbia

Abstract: Hail, bane of the agriculturist and insurance adjuster, is rarely noted as a cause of damage to forest trees. Yet, when severe hailstorms occur, damage to forest vegetation may be both dramatic and serious. We report here on the immediate effects of one hailstorm on recently planted white spruce (Picea glauca (Moench) Voss) and lodgepole pine (Pinus contorta Dougl. var. latifolia Engelm.) trees near the village of Upper Fraser in central British Columbia. ObservationsA drop in temperature from 65OF to 45°F imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1974
1974
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…). Abiotic disturbances like frost, wind, severe drought and hail are other important agents of defoliation in temperate forests (Grayburn ; Dobbs & McMinn ; Ozolincius & Stakenas ; Lorenz & Becher ), which also appear to cause more defoliation in deciduous than in evergreen species (Lorenz & Becher ). In cases of intense and unpredictable defoliation, herbivory tolerance is thought to be the most efficient strategy to adopt (van der Meijden, Wijn & Verkaar ; Haukioja & Koricheva ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…). Abiotic disturbances like frost, wind, severe drought and hail are other important agents of defoliation in temperate forests (Grayburn ; Dobbs & McMinn ; Ozolincius & Stakenas ; Lorenz & Becher ), which also appear to cause more defoliation in deciduous than in evergreen species (Lorenz & Becher ). In cases of intense and unpredictable defoliation, herbivory tolerance is thought to be the most efficient strategy to adopt (van der Meijden, Wijn & Verkaar ; Haukioja & Koricheva ).…”
Section: Introductionmentioning
confidence: 99%
“…The fast leaf economics strategy of deciduous species, associated with low toughness and high nutrient concentration and specific leaf area (SLA; Mooney & Gulmon 1982;Wright et al 2004), certainly makes leaves more susceptible to herbivory (Chabot & Hicks 1982;Pringle et al 2011). Abiotic disturbances like frost, wind, severe drought and hail are other important agents of defoliation in temperate forests (Grayburn 1957;Dobbs & McMinn 1973;Ozolincius & Stakenas 1996;Lorenz & Becher 2012), which also appear to cause more defoliation in deciduous than in evergreen species (Lorenz & Becher 2012). In cases of intense and unpredictable defoliation, herbivory tolerance is thought to be the most efficient strategy to adopt (van der Meijden, Wijn & Verkaar 1988;Haukioja & Koricheva 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Increased damaged levels substantially lead to reduced shoot diameter in years 2-4. Previous studies reported that recovery of the shoot growth of peach and apple fruit trees or pine trees was not completely occurred with leaf injury over 50% from hail in the following season due to the reduced synthesis of assimilates from lack of sources [16,23,24]. The number of shoots and shoot length of Japanese apricot trees showed similar trends to the peach trees, responding to the levels of DF and DF + IP in years 2-4 (Table 3).…”
Section: Subsequent Tree Damagementioning
confidence: 63%
“…Among the numerous forms of disturbance mimicked experimentally, canopy defoliation stands out as an important source of disturbance in forest ecosystems that has rarely been represented in largescale manipulation experiments despite its massive global impact and increasing extent (Anderegg et al 2015, Fei et al 2019. Defoliation can occur as a result of herbivory, pathogens, or through mechanical means (e.g., hailstorms or hurricanes; Dobbs andMcMinn 1973, Shiels et al 2014). Most extensive and severe defoliation events are related to insect pests, and patterns of defoliation timing and intensity vary, with cyclical, outbreak, and background herbivory all common in nature (Kautz et al 2017).…”
mentioning
confidence: 99%